2022
DOI: 10.3390/biomedicines10020483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clostridium butyricum on Gastrointestinal Infections

Abstract: Clostridium butyricum is a human commensal bacterium with beneficial effects including butyrate production, spore formation, increasing levels of beneficial bacteria, and inhibition of pathogenic bacteria. Owing to its preventive and ameliorative effects on gastrointestinal infections, C. butyricum MIYAIRI 588 (CBM 588) has been used as a probiotic in clinical and veterinary medicine for decades. This review summarizes the effects of C. butyricum, including CBM 588, on bacterial gastrointestinal infections. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 106 publications
0
30
0
Order By: Relevance
“…Several studies have reported that the uterine infusion or vaginal infusion of probiotics is effective in the treatment of endometritis [ 29 , 30 , 31 ]. C. butyricum has been shown to have potential protective or ameliorating effects on a variety of human and animal diseases, including gut-acquired infections, irritable bowel syndrome, inflammatory bowel disease, neurodegenerative disease, metabolic disease, and colonic rectal cancer [ 23 , 32 ]. However, the effect of C. butyricum on endometritis has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that the uterine infusion or vaginal infusion of probiotics is effective in the treatment of endometritis [ 29 , 30 , 31 ]. C. butyricum has been shown to have potential protective or ameliorating effects on a variety of human and animal diseases, including gut-acquired infections, irritable bowel syndrome, inflammatory bowel disease, neurodegenerative disease, metabolic disease, and colonic rectal cancer [ 23 , 32 ]. However, the effect of C. butyricum on endometritis has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that C. butyricum and its culture supernatant had an antibacterial effect. The antibacterial effect of C. butyricum has been reported in several studies [ 32 , 36 ]. Our results once again proved the data of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, probiotics including Bacteroides (e.g., Bacteroides fragilis ), Clostridium butyricum , and Saccharomyces boulardii are also being developed as the next generation of probiotic chassis. These probiotics possess good anti-infection properties, protect gut barrier function, regulate host immunity, and promote anti-inflammatory effects. , Moreover, they exhibit novel features. For example, Bacteroidetes are powerful colonizers of colonic crypts, which are inaccessible to common probiotics. C. butyricum has been used to treat antibiotic-associated diarrhea in many countries and can produce anti-inflammatory metabolites, such as butyrate and β-hydroxybutyrate, as well as spores to resist the harsh environment of the gut …”
Section: Chassismentioning
confidence: 99%
“…For example, in the setting of bacterial vaginosis (BV), another disease defined by overgrowth of a particular vaginal microbe which competes with beneficial Lactobacilli, the application of topical metronidazole followed by a constitution of a beneficial strain of L. crispatus, known as LACTIN-V, resulted in the presence of L. crispatus in nearly 80% of patients 12 weeks after initial treatment with relatively few side effects and decreased the risk of BV recurrence by 1/3 (Cohen et al, 2020). Other potential focused interventions to eliminate L. iners such as topical application of specific bacteriocins, lytic phage use, or probiotics have successfully been used to treat recurrent clostridium difficile and methicillin-resistant Staphylococcus aureus (MRSA) infections (Nataraj and Mallappa, 2021;Ariyoshi et al, 2022).…”
Section: Inersmentioning
confidence: 99%